Effect of Septal Deviation, Concha Bullosa and Haller’s Cell on Maxillary Sinus’s Inferior Pneumatization; a Retrospective Study - DUMLU, ASIM; NAMDAR PEKİNER, FİLİZ MEDİHA; GÖÇMEN, GÖKHAN; BORAHAN, MEHMET OĞUZ (My University, 2015)
Purpose : Maxillary sinus’s inferior pneumatization is a physiological process, which increase with time and accelerates following extraction. The aim of this study was to determine the prevalence of nasal septal deviation (NSD), concha bullosa (CB), and Haller’s cells (HC) and to examine the correlation of maxillary sinus inferior pneumatization (MSIP) with these anatomical variations. Material and Methods : 300 (150 m, 150 f) CBCT scans taken at the Marmara University School of Dentistry from 2011 to 2014 were retrospectively reviewed for the presence of CB, NSD, HC and MSIP. The correlation between pneumatization to the anatomic variants was then compared. Data were analyzed with a Chi-square test. Results : Of the 300 CBCT scans, 44.3% have CB, 37.3% NSD, 19.3% HC and 27.7% MSIP. There was no statistical significancewhen comparing the relationship of patients with CB, NSD, HC and pneumatization. Conclusion : NSD, CB and HC do not have a definite role on sinus’s inferior pneumatization. Further studies should be conducted including potential factors related pneumatization with more sample size for further correlation with NSD, CB,HC.